Designing bike-friendly cities: Interactive effects of built environment factors on bike-sharing. (April 2023) - Wang, Lan; Zhou, Kaichen; Zhang, Surong; Moudon, Anne Vernez; Wang, Jinfeng; Zhu, Yong-Guan; Sun, Wenyao; Lin, Jianfeng; Tian, Chao; Liu, Miao
Highlights: Geographical detector models facilitate a comprehensive approach to urban Design. Interaction detector measures combined effects of the built environment on Cycling. Street network centrality has the largest explanatory power on cycling. A sense of enclosure defined by streetscape elements encourages cycling. Abstract: Designing bike-friendly cities could promote health and mitigate climate change. Most studies of the association between the built environment and cycling used the "5Ds" framework and linear modeling. However, the built environment exerts complex influences on travel behavior. To better inform urban design for cycling, this study employed geographical detector models that quantify the explanatory power of individual and interactively paired built environment factors on bike-sharing. Data came from 6.5 million bike-sharing orders in Shanghai. Expectedly, we found that street network centrality and important facilities like supermarkets and libraries have the greatest independent and interactive effects. More surprisingly, streetscape elements, including sky view and building frontage, offered significantly higher explanatory power when paired with each other or with street network centrality and important facilities. By identifying the overlooked interactive effects of urban environment factors, the study provides guidance for urban designers to consider combinations of factors that effectively promote cycling.